Rancang Bangun Aplikasi Penentuan Harga Pokok Produksi pada UD Eka - Bujana, Dwiki Andhika Satria; Widodo, Arifin Puji; Sutanto, Teguh (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
UD Eka is a manufacturing company who produces shoes and sandals, also footwear raw materials like soles and heels. UD Eka was established in 1990 and located in Krian Sidoarjo. Currently, the company does not calculate production costs, the company only estimates the cost of production for charged to each product. There is no calculation of production costs, making the company has no fixed basis in setting the selling price. Based on thats problems, this research result is make the application of the determination of cost of goods manufactured that can produce information on raw material costs, direct labor costs, factory overhead costs and cost of production. The method of determining the cost of production in this application is use full costing method. This method is chosen because this method concerns all production costs both fixed and variable in calculating the cost of production. So, the cost of production produced reflects the actual costs incurred in production activities and can determine the selling price in accordance with the desired profit. Based on the test results, the applications that have been built can generate direct material costs, direct labor costs, fixed overhead costs, variable overhead costs and cost of production.